Combined use of venoarterial extracorporeal membrane oxygenation and intra-aortic balloon pump after cardiac arrest. (October 2021) - Kuroki, Norihiro; Nagao, Ken; Otsuka, Toshiaki; Kuwabara, Masanari; Nakata, Jun; Takayama, Tadateru; Hosokawa, Yusuke; Ashida, Tadashi; Suzuki, Kou; Yamamoto, Takeshi; Takayama, Morimasa
Abstract: Objectives: We investigated whether intra-aortic balloon pump (IABP) combined with venoarterial extracorporeal membrane oxygenation (VA-ECMO) was associated with favourable neurological outcomes for patients after the return of spontaneous circulation (ROSC). Moreover, we evaluated the aetiology of cardiac arrest on the effectiveness of this therapy in a sub-study. Background: There is insufficient research on the optimal combination of machines for patients after ROSC is not established. Methods: This is a large-scale, multicentre, 30-day cohort study. Among 80, 716 patients who delivered to the emergency room, 935 patients treated with VA-ECMO after ROSC were included using the data from the Tokyo Cardiovascular Care Unit Network Registry between 2010 and 2017. The study patients were stratified according to the use of IABP [the ECMO + IABP group (n = 762) vs. the ECMO-alone group (n = 173)]. We also evaluated the cause of cardiac arrest [acute coronary syndrome (ACS) and non-ACS] in the sub-study. To adjust the patients' backgrounds, we used the propensity score matching for additional analyses. The endpoint was 30-day favourable neurological outcome. Results: The ECMO + IABP group showed significantly better neurological outcomes than the ECMO-alone group (crude; 35% vs. 25%; log-lank P < 0.001). In the ACS subgroup, the ECMO + IABP group showed significantly better neurological outcome (crude; 34% vs. 18%; log-lank P < 0.001), but not in the non-ACS subgroup (crude; 38% vs. 32%; log-lank P = 0.11). These results are similar after adjustments to their backgrounds using propensity matching. Conclusions: Compared to VA-ECMO alone, the combined use of VA-ECMO and IABP is associated with better neurological outcomes after ROSC, especially in complicated ACS.